2010
DOI: 10.1002/uog.7555
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal findings and differential diagnosis of scimitar syndrome and pulmonary sequestration

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 28 publications
(17 reference statements)
2
16
0
Order By: Relevance
“…In reconstruction (d) shows the systemic arterial supply (white arrow) and the pulmonary venous drainage (white arrowhead). Low power view of intralobar sequestration (e) shows pleural fibrosis and mild inflammatory changes in pulmonary parenchyma with mucus in some alveoli (H&E, 940) the literature, the diagnostic accuracy of this method ranges between 56 and 77 %, very similar to our results [10,[15][16][17].…”
Section: Discussionsupporting
confidence: 88%
“…In reconstruction (d) shows the systemic arterial supply (white arrow) and the pulmonary venous drainage (white arrowhead). Low power view of intralobar sequestration (e) shows pleural fibrosis and mild inflammatory changes in pulmonary parenchyma with mucus in some alveoli (H&E, 940) the literature, the diagnostic accuracy of this method ranges between 56 and 77 %, very similar to our results [10,[15][16][17].…”
Section: Discussionsupporting
confidence: 88%
“…SS and PAPVC cases were excluded from the meta‐analysis, but included in the systematic review. The characteristics of the studies reporting on SS are reported in Table S2 and of those on PAPVC in Tables S3 and S4.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 15 studies 5,8,9,12,[18][19][20][21][22][23][24][25][26][27] , including the present one, reporting on 71 patients were included in the systematic review and meta-analysis. Three additional studies [28][29][30] were included only in the systematic review and not in the meta-analysis. Characteristics of patients with a postnatally validated diagnosis of TAPVC are reported in Tables 1-3.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, Van de Laar recently described prenatal findings in a family with congenital pulmonary vein stenosis; three had markedly increased nuchal translucency (7–11 mm), and one had severe hydrops and pleural effusions14. Bhide and colleagues15 also showed that obstructed partial anomalous pulmonary venous connection in pulmonary sequestration can lead to pleural effusions large enough to require fetal intervention for hydrops. Indeed, obstructed TAPVC may prove to be a rare cause of increased nuchal translucency and/or pleural effusions in fetuses.…”
Section: Discussionmentioning
confidence: 99%